2011
DOI: 10.1021/jp201703c
|View full text |Cite
|
Sign up to set email alerts
|

Room-Temperature Ionic Liquids Discerned Via Nitroxyl Spin Probe Dynamics

Abstract: The temperature dependence of the rotational correlation times, τ(c), of the nitroxide spin probes TEMPO, TEMPOL, TEMPAMINE, and Fremy's salt in the ionic liquids 1-ethyl-3-methylimidazolium ethylsulfate, 1-butyl-3-methylimidazolium hexafluorophosphate, 1-ethyl-3-methylimidazolium tetrafluoroborate, and 1-butyl-3-methylimidazolium tetrafluoroborate is scrutinized. The rotation correlation times vary between 54 and 1470 ps at 300 K. Within a temperature range of 280-380 K, the rotational tumbling is well descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
101
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(111 citation statements)
references
References 77 publications
7
101
2
1
Order By: Relevance
“…[53][54][55][56][57]). The time modulation of the magnetic tensors gives three types of relaxation terms, namely secular, pseudosecular and non-secular (fluctuating respectively at zero frequency, at the nuclear Larmor frequency and at the electron Larmor frequency).…”
Section: Discussionmentioning
confidence: 99%
“…[53][54][55][56][57]). The time modulation of the magnetic tensors gives three types of relaxation terms, namely secular, pseudosecular and non-secular (fluctuating respectively at zero frequency, at the nuclear Larmor frequency and at the electron Larmor frequency).…”
Section: Discussionmentioning
confidence: 99%
“…This dispersion contribution previously presented in Figure 12 of ref 43 and Figures S2–S4 in the Supporting Information could be explained by the Freed et al approach 44 which is based on the stochastic Liouville equation and involves a relaxation matrix with all contributions: secular, pseudo-secular and non-secular. Mladenova et al 26 also suggested that the dispersion signal is of pseudo-secular origin; in other words, from the off-diagonal contributions to the relaxation superoperator. For this reason, the height of the dispersion signal is directly proportional to the rotational correlation time; the longer the rotational correlation time, the greater the dispersion component in the EPR lines.…”
Section: Methodsmentioning
confidence: 99%
“…The activation energy for the probe’s rotational tumbling in each solvent were reasonably close to those of the ILs viscous flow. 26 On the other side, Miyake et al 23 have observed that the rotational correlation time of proxyl radicals in [C 4 mim][BF 4 ] and [C 4 mim][PF 6 ] obeys a fractional SED law, which they compared with the rotation of TEMPO in supercooled liquids.…”
Section: Introductionmentioning
confidence: 99%
“…CW and pulse EPR of nitroxide spin probes is extensively used in biochemical applications, [31][32][33] and has also been applied in a series of works to reveal peculiarities of ILs. [34][35][36][37][38][39][40][41][42][43][44] In particular, it was demonstrated that microscopic viscosity experienced by radicals might be considerably different from the corresponding macroscopic value. 28,34 The crystallization, glass formation and softening of ILs vs. temperature were also addressed.…”
Section: Introductionmentioning
confidence: 99%
“…[34][35][36][37][38][39][40][41][42][43][44] In particular, it was demonstrated that microscopic viscosity experienced by radicals might be considerably different from the corresponding macroscopic value. 28,34 The crystallization, glass formation and softening of ILs vs. temperature were also addressed. 42 In some cases, high-field pulse EPR was applied to characterize the ways of nitroxide dissolvation in ILs and IL-water mixtures.…”
Section: Introductionmentioning
confidence: 99%